MENGEMBANGKAN INDIKATOR KUALITAS PELAYANAN KESEHATAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Quality care constitutes an important aspect to be pursued within the "Healthy Indonesia 2010" vision. In order to enable assessment of changes in the quality of care over time, there is a need for developing quality indicators. Quality indicators are specific and measurable elements of practice, developed on the basis of evidences and/or concensus, that can be used to assess the quality of care. Some factors influence the development of quality indicators: (1) Stakeholders' perspectives